ANALYSIS OF PSYCHOSOCIAL STATUS AND QUALITY OF LIFE IN THE ELDERLY WITH OSTEOARTHRITIS DURING THE COVID-19 PANDEMIC: A CROSS SECTIONAL STUDY - Mohd Syukri; Dewi Masyitah; Mashudi; Lailatul Fadilah (OPI Napoli, 2023)
Introduction: Along with increasing age, there will also be an increasing tendency to get sick and have physical limitations (disabilities) due to a drastic decline in physical abilities. These conditions are the leading cause of high mortality and morbidity in the elderly, especially during the Covid-19 pandemic. The current study aims to analyze the relationship between psychosocial status and the quality of life of the elderly with osteoarthritis during the Covid-19 pandemic. Materials and Methods: This cross-sectional study was located at a nursing home in Jambi, involving 351 randomly selected participants. Measure the psychosocial status of the elderly using the Indonesian version of the Self Reporting Questionnaire (SRQ) and the quality of life using the Indonesian version of the World Health Organization Quality of Life-Old (WHOQOL - OLD) questionnaire. Results: Most elderly have a good quality of life, as many as 229 (65.1%), while a poor quality of life, as many as 30 people (8.5%). In the psychosocial variables, most respondents did not experience mental health disorders, as many as 260 people (74.1%). The Mann-Whitney test showed a significant relationship between Quality of Life and Psychosocial Status, in particular we obserbed in subjects without mental disorders in comparison to subjects with mental disorders a better quality of life, i.e. the elderly who do not suffer from mental disorders will show a tendency for a good quality of life. Conclusions: Psychosocial status related to quality of life in the elderly with osteoarthritis during the Covid-19 pandemic. The elderly who do not suffer from mental disorders will show a tendency for a good quality of life.